2017
DOI: 10.1038/s41598-017-11172-6
|View full text |Cite|
|
Sign up to set email alerts
|

Novel detection of post-translational modifications in human monocyte-derived dendritic cells after chronic alcohol exposure: Role of inflammation regulator H4K12ac

Abstract: Previous reports on epigenetic mechanisms involved in alcohol abuse have focus on hepatic and neuronal regions, leaving the immune system and specifically monocyte-derived dendritic cells (MDDCs) understudied. Our lab has previously shown histone deacetylases are modulated in cells derived from alcohol users and after in vitro acute alcohol treatment of human MDDCs. In the current study, we developed a novel screening tool using matrix assisted laser desorption ionization-fourier transform-ion cyclotron resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 69 publications
2
8
0
Order By: Relevance
“…These results are fully in line with a recent study showing a 350 similar increase in the total histone content in pluripotent versus differentiated 351 cells (Karnavas et al, 2014). An additional study also showed that histone content in 352 monocytic-derived DCs can vary significantly upon treatment with different 353 immunological stimuli (Parira et al, 2017). As H2B is directly involved in DNA 354 compaction, our results reveal that chromatin is indeed in a more accessible conformation 355 during early stages of DC differentiation, i.e., at day 0 DCs.…”
Section: Chromatin Compaction Increases Upon DC Differentiation and Csupporting
confidence: 80%
“…These results are fully in line with a recent study showing a 350 similar increase in the total histone content in pluripotent versus differentiated 351 cells (Karnavas et al, 2014). An additional study also showed that histone content in 352 monocytic-derived DCs can vary significantly upon treatment with different 353 immunological stimuli (Parira et al, 2017). As H2B is directly involved in DNA 354 compaction, our results reveal that chromatin is indeed in a more accessible conformation 355 during early stages of DC differentiation, i.e., at day 0 DCs.…”
Section: Chromatin Compaction Increases Upon DC Differentiation and Csupporting
confidence: 80%
“…Data were acquired and analyzed with Amnis® FlowSight® Imaging Flow Cytometer and IDEAS software. Staining, image collection, and analysis were carried out according to manufacturer’s protocol and as previously published 21 , 22 . As seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further, a novel TIP60 inhibitor, NU9056 was being investigated for its effects and role in human neuronal cells (Tan et al, 2016a) . Based on the literature, NU9056 was selected and viability assay like trypan blue and XTT assay was carried out to select 50nM as an optimum concentration for treatment in human MDDCs (data available in publication Parira et al, 2017c). Post differentiation, MDDCs were pre-treated with 50nM NU9056 for 2 hours and then cells receiving alcohol treatment were treated with 0.2% EtOH for five days.…”
Section: Chronic Treatment With Histone Acetyltransferase Inhibitor Nmentioning
confidence: 99%
“…analyzed according to manufacturer instructions with the RayBiotech inflammation arrays (RayBiotech, Norcross, GA, USA) as previously described by us (Agudelo et al, 2013, Parira et al, 2017c, Parira et al, 2017a. Briefly, supernatants from cells after 5-day posttreatment with NU9056, 0.2% EtOH and 0.2% EtOH + NU9056 and an untreated control were assayed for the experiment.…”
Section: Cytokine Array and Mcp2 Elisa The Expression Of 48 Inflammatmentioning
confidence: 99%
See 1 more Smart Citation